FAK is overexpressed in keratocystic odontogenic tumor: a preliminary study. (6th January 2017) - Sarode, Sachin C; Sarode, Gargi S; Choudhary, Shakira; Patil, Shankargouda
Abstract : Background: Focal adhesion kinase (FAK) is an important mediator of cell adhesion, growth proliferation, survival, angiogenesis, and migration. FAK is overexpressed in many locally invasive and malignant lesions including oral cancer. Looking at the tumorigenic nature of keratocystic odontogenic tumor (KCOT), which involves local invasion, proliferation, and recurrence, we hypothesized strong expression of FAK in the epithelial lining of KCOT. Materials and Methods: 34 KCOTs, 11 orthokeratinized odontogenic cysts (OOCs), 25 radicular cysts (RCs), 17 dentigerous cysts (DCs), and 25 dental follicles (DFs) were retrieved from archives and subjected to the immunohistochemical analysis using FAK antibody. Results: In KCOT, strong expression was observed in 22 (62.8%) cases followed by weak and negative expression in 9 (25.71%) and 4 (11.4%) cases, respectively. Negative expression was seen in 7 (63.63%) cases of OOC, while 4 (36.36%) showed weak expression. In case of RC, 20 (80%) cases displayed negative expression and 4 (16%) and 1 (4%) cases showed weak and strong expressions, respectively. In case of DC, negative expression was seen in 14 (82.35%) cases and weak expression in 3 (17.64%) cases. DF was characterized by negative [21 (84%)] and weak expression [4 (16%)]. Nuclear expression of FAK was seen only in KCOT (11 cases). There was statistically significant higher FAK expression in KCOT as compared to OOC, RC, DC, and DF ( P < 0.00001). Conclusion: FAK molecule could be an important player in tumorigenesis of KCOT and thus is a potential target for future drug development.